Analisa Konsumsi Energi Listrik Rumah Dengan Kendali Otomatis - Benriwati Maharmi (SainETIn : Jurnal Sains, Energi, Teknologi, dan Industri, 2018)
An automatic control of the home lights can save energy consumption, thereby reducing the cost of electricity payment. This paper aims to test the Cost Saving Energy Electricity tool with automatic control of home lighting using Arduino Mega 2560 microcontroller, because it has advantages that the number of input / output a lot so that the flexibility of the controlled light load can be more. The control system used a RTC (Real Time Clock) method, which has excess timer that can always be up-to-date. Also, the ACS-712 Current Sensor can measure the outflow current on the light load to be displayed by LCD and the Relay Module can control automaticly On/Off. However, problems experienced when using the On/Off switch contact manually that was turn on or off the light, which at the different clocks due to human negligence so that the power consumption being not well controlled. Test results that have been done for a month with a maximum load of 300 Watt was obtained electric power consumption for reading on kWh meter by using cost saving energy tool of 61.4 kWh while in the manual system of 85.7 kWh. Furthermore, it got the power difference of 24.3 kWh. The value of electricity cost savings of 35.655 (TDL, Rp 1,467.28 / kWh). Therefore, the use of cost saving energy to control home lighting automatically proved more energy efficient than the manual system using the On/Off switch.